Так когда же хазары приняли иудаизм? - Бубенок, О.Б. (Хазарский альманах, 2016)
Так, на сегодняшний день существует несколько гипотез относительно времени и обстоятельств иудаизации хазар. Еще в начале ХХ в. Й. Маркварт высказал мнение, что не более чем за сто лет до хазарской миссии Константина в 861 г. хазарская верхушка исповедовала иудаизм . Еще более раннюю дату предложил более 60 лет назад М. Данлоп. Исследователь, руководствуясь данными Иегуды Галеви, не нашел ничего лучшего, как датировать это событие приблизительно 740 г. Однако большинство современных исследователей отнесли иудаизацию хазар к рубежу VIII–IX вв.. Прежде всего, они руководствовались сообщением ал-Мас‘уди, что «царь хазар» перешел в иудейскую веру во времена правления халифа Харуна ар-Рашида, который был при власти с 786 по 814 г. Именно этой точки зрения долгое время придерживалось большинство исследователей. Однако более десяти лет назад французский ученый К. Цукерман предложил более позднюю дату – 861–865 гг. To the present time we have several opinions concerning the date of the Khazar’s conversion to Judaism. So, there an opinion has prevailed among the researchers (O. Pritsak, M. I. Artamonov, B. N. Zakhoder, A. P. Novoseltsev) that the Khazars’ conversion to Judaism took place during the reign of Harun al-Rashid, in the late 8th century or the early 9th century. It was based on the data of some Arabic sources of the 10th century – foremost on one book by Al-Mas‘udi. However, A. Krymsky and C. Zuckerman, alluding to the data of some Christian sources – foremost “Life of Saint Constantine”, argues that it must have happened after the famous mission of Constantine (Cyril) to the Khazars (in 861). Beside, A. Krymsky relied mostly on the data of the Arab authors of the late 9th century and the early 10th century – Ibn al-Faqih, Ibn Khordadbeh, Al-Jahiz and Al-Bakri (the 11th century). Concerning the information of Al-Mas‘udi about the judaization of the ruling stratum of the Khazars during the reign of Harun al-Rashid, A. Krymsky considered that the term “malik” was used with respect to one of the khagan’s noblemen (possibly “beg” in future), and not to the khagan himself.